A Study of Lightning Activities and Their Impact in the Ionosphere Over Nepal - Pandit, Drabindra; Poudel, Prasil; Shoni, Romash; Budha Chhetri, Nikesh; Adhikari, Binod; Chapagain, Narayan Prasad; Sharma, Shriram (Amrit Research Journal, 2024)
The ionosphere is a system that can experience dynamical perturbation due to external influences from solar dynamics and activities: geomagnetic storms, solar radiation and lower atmospheric events such as thunderstorms and gravity waves. In this study we have analyzed the changes in the Total Electron Content (TEC) in relation with the thunderstorm activities taking into account of the lightning stroke density as a perturbing factor. The data pertaining to TEC have been obtained from GNSS whereas the lightning stroke data have been obtained from VAISALA’s GLD 360. Analyzing the data from 2015 to 2018 the variation of TEC in association with stroke density during the pre-monsoon season was found to be significant for the period of study (pre-monsoon period). This implies that thunderstorms play a significant role in the ionospheric perturbation that may result in the disruption in communication. The outcome of this study can lay the foundation on the work to investigate the extent of perturbation and hence the communication disruption being emanated by thunderstorms.